‘Fatta l’Italia, facciamo gli Italiani’. Appunti su una massima da restituire a d’Azeglio - Gigante, Claudio (Incontri. Rivista europea di studi italiani, 2011)
‘Fatta l’Italia, facciamo gli Italiani’Notes on the reattribution of a maxim to d’AzeglioIn the past few years, since the 1993 publication of a volume edited by Simonetta Soldani and Gabriele Turi, it has been taken as a given that the phrase that had traditionally been attributed to Massimo d’Azeglio (‘Fatta l’Italia, facciamo gli Italiani’) is in fact apocryphal. It was Ferdinando Martini, in 1896, who had ascribed it to the Piemontese statesman who had died thirty years prior, on the basis of a spurious passage that appeared in the contemporary edition of the Ricordi (‘s’è fatta l’Italia, ma non si fanno gl’Italiani’). The sentence, in reality, circulated earlier than was held by Martini. De Sanctis, in a series of lectures held at the University of Naples in 1872-1873, used the phrase to synthesize d’Azeglio’s thought, and in Leone Capri’s Italia vivente (1878) the maxim already appears in the form which would later be widely spread. However, what is relevant above all is the phrase that reappears in a similar form in various pieces by d’Azeglio himself (e.g., a passage of the Ricordi that is surely ‘authentic’, regarding Ettore Fieramosca reads: ‘Io pensavo [...] che bisogna far gli Italiani se si vuol avere l’Italia […]’) If not in the exact wording (and this point is also debatable), the maxim, interpreted opportunely, can, if only in spirit, be attributed to d’Azeglio.